Determination of the role of aerobic and anaerobic training at different altitude on hypoxia-induced factor 1, hemoglobin, iron, erythropoietin, hepcidin, and nitric oxide - Onturk, Ugur; Cinar, Vedat; Sarikaya, Mucahit; Alp, Hamit Hakan; Akbulut, Taner; Chaverri, Diego; Migliaccio, Gian Mario (Oxford Univ Press, 2025)
Introduction or background Altitude training is a well-established strategy for improving athletic performance, particularly in endurance sports. Hypoxic exposure induces physiological adaptations through oxygen sensing and erythropoietic mechanisms. However, the comparative effects of aerobic and anaerobic training on hematological and biochemical markers under different altitude conditions have not yet been adequately investigated.Sources of data This prospective cohort study included 24 trained male athletes (aged 19-23) who were randomly assigned to aerobic or anaerobic training groups (n = 12 per group). Training was conducted at simulated altitudes of 0 m, 1700 m, 2450 m, and 3200 m for 8 weeks. Biomarkers such as hypoxia-induced factor 1-alpha (HIF-1 alpha), hemoglobin, erythropoietin (EPO), iron, hepcidin, and nitric oxide (NO) were measured using ELISA and standard biochemical methods.Areas of agreement Consistent with previous literature, both aerobic and anaerobic training resulted in altitude-induced increases in hemoglobin levels. Aerobic training was associated with earlier activation of hypoxia-related markers such as HIF-1 alpha and NO, supporting the role of moderate altitude exposure in stimulating adaptive molecular responses.Areas of controversy While EPO is generally expected to increase with altitude exposure, this study found a decrease in EPO levels across altitudes in the aerobic group, while a significant increase was observed only at 3200 m in the anaerobic group. Interpretation of hepcidin dynamics also differs between training modalities, highlighting the complexity of iron regulation under hypoxic stress.Growing points This study highlights the different timing and magnitude of biomarker responses to aerobic and anaerobic training at various altitudes. It suggests that aerobic exercise triggers earlier molecular responses, while anaerobic training elicits delayed or blunted adaptations.Areas timely for developing research Further research is needed to optimize altitude training protocols tailored to specific exercise modalities and targeted physiological adaptations. Future studies could examine gender differences, longer training durations, and additional markers of oxidative stress and inflammation to expand on these findings.
Keywords: HIF-1 alpha EPO regulation; hepcidin-iron metabolism; altitude training adaptations; aerobic vs anaerobic responses